Optimal timing for blastomere biopsy of 8-cell embryos for preimplantation genetic diagnosis. Issue 1 (20th November 2017) - Kalma, Y; Bar-El, L; Asaf-Tisser, S; Malcov, M; Reches, A; Hasson, J; Amir, H; Azem, F; Ben-Yosef, D
Abstract: STUDY QUESTION: What is the optimal timing for blastomere biopsy during the 8-cell stage, at which embryos will have the best implantation potential? SUMMARY ANSWER: Fast-cleaving embryos that are biopsied during the last quarter (Q4) of the 8-cell stage and are less affected by the biopsy procedure, and their implantation potential is better than that of embryos biopsied earlier during the 8-cell stage (Q1–Q3). WHAT IS KNOWN ALREADY: Blastomer biopsy from cleavage-stage embryos is usually performed on the morning of Day 3 when the embryos are at the 6- to 8-cell stage and is still the preferred biopsy method for preimplantation genetic diagnosis (PGD) for monogentic disorders or chromosomal translocations. Human embryos usually remain at the 8-cell stage for a relatively long 'arrest phase' in which cells grow, duplicate their DNA and synthesize various proteins in preparation for the subsequent division. STUDY DESIGN, SIZE, DURATION: This is a retrospective cohort study. The study group (195 embryos) included all 8-cell stage embryos that underwent blastomere biopsy for PGD for monogenetic disorders and chromosomal translocations in our unit between 2012–2014 and cultured in the EmbryoScope until transfer. The control group (115 embryos) included all embryos that underwent intracytoplasmic sperm injection without a biopsy during the same period. PARTICIPANTS/MATERIALS, SETTING, METHODS: The 8-cell stage was divided into four quarters: the first 5 h post-t8 (Q1), 5–10 h post-t8 (Q2), 10–15 h post-t8 (Q3) and at 15–20 h post-t8 (Q4). Non-biopsied control embryos were divided into four equivalent quarters. Embryos were evaluated for timing of developmental events following biopsy including timing of first cleavge after biopsy, timing of comapction (tM) and start of blastulation (tSB). Timing of these events were compared between PGD and control embryos, as well as with 56 PGD implanted embryos with Known Implantation Data (PGD-KID-positive embryos). MAIN RESULTS AND THE ROLE OF CHANCE: Embryos that were biopsied during Q3 (10–15 h from entry into 8-cell stage) were delayed in all three subsequent developmental events, including first cleavage after biopsy, compaction and start of blastulation. In contrast, these events occurred exactly at the same time as in the control group, in embryos that were biopsied during Q1, Q2 or Q4 of the 8-cell stage. The results show also that embryos that were biopsied during Q1, Q2 or Q3 of the 8-cell stage demonstrated a significant delay from the biopsied implanted embryos already in t8 as well as in tM and tSB. However, embryos that were biopsied during Q4 demonstrated dynamics similar to those of the biopsied implanted embryos in t8 and tM, and a delay was noticed only in the last stage of tSB. LIMITATIONS, REASONS FOR CAUTION: This is a retrospective study that is limited to the timing of biopsy that is routinely performed in the IVF lab. A prospective study in which biopsy will be performed at a desired timing is needed in order to differ between the effect of biopsy itself and the cleavage rate of the embryo. WIDER IMPLICATIONS OF THE FINDINGS: Our findings showed that blastomere biopsy can be less harmful to further development if it is carried out during a critical period of embryonic growth, i.e during Q4 of the 8-cell stage. They also demonstrated the added value of time-lapse microscopy for determining the optimal timing for blastomere biopsy. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the routine budget of our IVF unit. TRIAL REGISTRATION NUMBER: N/A.